Penegakan Rasa Aman Melalui Intervensi Kemanusiaan - Erliyana, Anna (UI Scholars Hub, 2006)
When a state has no longer guaranteed the implementation of personal rights, social contract automatically will decease. The decease of social contract will cause the failing of state sovereignty. In this case, state is no longer has philosophic fundamental as supporting state. As a consequence of a state cannot protect its citizens’ rights, the enforcement of state sovereignty merely can be done through external hand; this is the part when the role humanity begins to play. Humanity intervention will automatically stop when the norm and humanity law are enforced in the state and social contract are reconstructed.